VD_FINDINFO Décision / 2014 / 508 vom 12. Juni 2014 - VD Tribunal cantonal (2014)
RÉDUCTIONEN GÉNÉRAL, MOTIF, TORT MORAL, INDEMNITÉ PLEINE ET ENTIÈRE, INDEMNITÉ ÉQUITABLE | 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH), 430 CPP (CH)